Cord Blood Levels of Spexin, Leptin, and Visfatin in Term Infants Born Small, Appropriate, and Large for Gestational Age and Their Association with Newborn Anthropometric Measurements - Yücel Pekal; Bayram Özhan; Yaşar Enli; Özmert M.A. Özdemir; Hacer Ergin (JCRPE, 2022)
INTRODUCTION: Children born small for gestational age (SGA) are at risk of future obesity and associated comorbidities. Therefore the identification of risk factors and novel biomarkers which are associated with this risk are needed for early detection and to improve preventive strategies. Spexin (SPX), a novel neuropeptide that is involved in the regulation of obesity and fat metabolism, is a candidate biomarker for predicting obesity and related comorbidities at an early age. The aim of this study was to investigate serum levels of SPX in term infants born small, appropriate, and large for gestational age (LGA) and its association with newborn anthropometric measurements. METHODS: One hundred and twenty term newborn babies classified as SGA, appropriate for gestational age (AGA), or LGA and their mothers were included. SPX, leptin and visfatin were measured in cord blood and maternal serum by enzyme-linked immunosorbent assay. RESULTS: Fifty-six (46.7%) neonates were girls and 64 (53.3%) were boys. The mean birth weight was 3170.70±663 g, birth length was 48.9±2.79 cm, and head circumference was 34.5±1.67 cm. Birth weights, lengths, and head circumferences of the neonates in the SGA, AGA, and LGA groups were significantly different. Cord blood SPX and leptin levels in the SGA groups were significantly lower than those of both the LGA and AGA groups. Cord blood visfatin levels were significantly lower in the AGA group than the LGA and SGA groups. Maternal SPX levels of SGA babies were significantly lower than those of the mothers in both the LGA and AGA groups, but no significant difference was observed between the SGA and LGA groups. Maternal visfatin levels of the AGA babies were significantly higher than the maternal levels of SGA and LGA groups. There was no difference in terms of maternal leptin levels. Cord blood SPX and leptin levels were positively correlated with birth weight, length and head circumference. Birth weight increased significantly in line with maternal pregestational body mass index. DISCUSSION AND CONCLUSION: The lowest SPX levels were found in the SGA babies and cord SPX level was significantly correlated with newborn length, weight, and head circumference.